2010
DOI: 10.1111/j.1756-5391.2010.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving reporting of adverse events and adverse drug reactions following injections of Chinese materia medica

Abstract: The current reporting format of ADR/AE in clinical CM injections is not standardized. Much fundamental information of ADR/AE following CM injection is therefore missing. A standard reporting format for ADR should be developed, and should include the following: (1) a title mentioning adverse effects and safety; (2) a structured abstract including adequate information about the patient and the disease treated, the drug used, the specific ADR/AE, physician response to the ADR/AE, and result of management; (3) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 7 publications
0
15
1
Order By: Relevance
“…Secondly, the reported discomforts within 1 week after injections for CTS in the present study were different from the complications or discomforts described in other studies (18,19). This discrepancy could be avoided in the future by developing a standardized method for reporting CTS injection complications (42)(43)(44). Thirdly, the dropout rates of both groups in our study were higher than the accepted values in other randomized controlled trials.…”
Section: Discussioncontrasting
confidence: 70%
“…Secondly, the reported discomforts within 1 week after injections for CTS in the present study were different from the complications or discomforts described in other studies (18,19). This discrepancy could be avoided in the future by developing a standardized method for reporting CTS injection complications (42)(43)(44). Thirdly, the dropout rates of both groups in our study were higher than the accepted values in other randomized controlled trials.…”
Section: Discussioncontrasting
confidence: 70%
“…While reporting of ADR following CHM injection is becoming more and more common, the reporting quality is of concern. A standard reporting format for ADR has been developed [44] and we suggested that improvement of reporting of adverse events and ADRs of SMI may follow up. Fourth, SMI is widely used in the treatment of various disorders and seems generally safe.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the safety of herbal patent injection itself has become a major concern to both national health authorities and the general public [59] . A standard reporting format for adverse drug reactions (ADR) has been developed [60] , and we suggest that improvement of the reporting of adverse events and ADRs of PBCRBS should be closely followed. Fourthly, improvement in the methodological quality of primary RCTs is still crucial for future clinical studies.…”
Section: Implications For Further Researchmentioning
confidence: 99%